Nomadic Memory in Aleksandar Hemon’s Memoirs - Rubén Peinado-Abarrio (European Journal of American Studies)
This article focuses on Bosnian-American author Aleksandar Hemon’s two 2019 memoirs published in one volume, My Parents: An Introduction and This Does Not Belong to You. Specifically, it applies Rosi Braidotti’s notion of nomadic memory to Hemon’s telling of his and his family’s life stories. Analyzed with the tools provided by critical posthumanism, Hemon’s nonfiction becomes an example of remembering in what Braidotti calls a minority-mode. He presents the migrant as a subject-in-becoming, belonging to their community thanks to the workings of a transgenerational, nonlinear memory, operating in a time continuum where stable identities are deterritorialized and creative ways to access an unavailable past are generated. In Hemon’s writing, identity is rooted in concentric homelands, and the truth of the memory resides in the affects it provokes and sustains. Opposing the static authority of the past and any fixed notion of the self, Hemon understands the past as a cultural practice deposited in bodies and rituals, as a home apparently beyond reach to which the migrant reconnects through the resources of the imagination.